Not all investors are the same: Evidence from investor holdings of local-currency debt in Indonesia - Hosny , Amr (Asian Journal of Economics and Empirical Research, 2024)
This paper examines the global and domestic factors driving different investor holdings of local currency (LC) sovereign debt in Indonesia. Using an autoregressive distributed lag co-integration approach, using monthly data for Indonesia over 2002M12-2022M12, we find that non-resident holdings of LC debt in Indonesia are mostly driven by global factors such as commodity prices and volatility in global bond markets, while domestic investors (such as domestic banks and institutional investors) are mostly driven by higher debt security issuances and Bank of Indonesia (BI) acts as a residual financier under adverse conditions. We also find evidence that foreign investors follow the "benchmark effect" and are attracted by higher domestic yields. Results are mostly robust to different specifications. These results call for a further deepening of the investor base, especially domestic nonbanks, to support market depth and reduce volatility.